Urban adaptation, strategies and projects. The gap between policies and their implementation - Guido Emilio Rossi (Agathón)
The increasing impacts of climate change are pushing cities to take paths towards adaptation and resilience. The adaptation, due to its systemic nature, is multi-scalar: at the urban scale (macro-level) it is implemented through plans and strategies; on the scale of urban and architectural design (meso/micro), these strategies are implemented with concrete interventions. However, the action of some cities perceives a gap between the different levels. Through the analysis of adaptation in the urban areas of Miami and Rotterdam, the article aims to examine the gap that often exists between the strategy and the implementation, and the need for coherence between these that guarantees a real process of urban transformation towards greater resilience stages through systemic approaches.